Kinase Activity Is Not Required for G Protein–Coupled Receptor Kinase 4 Restraining mTOR Signaling during Cilia and Kidney Development. Issue 4 (26th April 2023) - Gerhards, Julian; Maerz, Lars D.; Matthees, Edda S. F.; Donow, Cornelia; Moepps, Barbara; Premont, Richard T.; Burkhalter, Martin D.; Hoffmann, Carsten; Philipp, Melanie
Abstract : Abstract : Significance Statement: G protein–coupled receptor kinase 4 (GRK4) regulates renal sodium and water reabsorption. Although GRK4 variants with elevated kinase activity have been associated with salt-sensitive or essential hypertension, this association has been inconsistent among different study populations. In addition, studies elucidating how GRK4 may modulate cellular signaling are sparse. In an analysis of how GRK4 affects the developing kidney, the authors found that GRK4 modulates mammalian target of rapamycin (mTOR) signaling. Loss of GRK4 in embryonic zebrafish causes kidney dysfunction and glomerular cysts. Moreover, GRK4 depletion in zebrafish and cellular mammalian models results in elongated cilia. Rescue experiments suggest that hypertension in carriers of GRK4 variants may not be explained solely by kinase hyperactivity; instead, elevated mTOR signaling may be the underlying cause. Background: G protein–coupled receptor kinase 4 (GRK4) is considered a central regulator of blood pressure through phosphorylation of renal dopaminergic receptors and subsequent modulation of sodium excretion. Several nonsynonymous genetic variants of GRK4 have been only partially linked to hypertension, although these variants demonstrate elevated kinase activity. However, some evidence suggests that function of GRK4 variants may involve more than regulation of dopaminergic receptors alone. Little is known about the effects of GRK4 on cellular signaling, and it is also unclear whether or how altered GRK4 function might affect kidney development. Methods: To better understand the effect of GRK4 variants on the functionality of GRK4 and GRK4's actions in cellular signaling during kidney development, we studied zebrafish, human cells, and a murine kidney spheroid model. Results: Zebrafish depleted of Grk4 develop impaired glomerular filtration, generalized edema, glomerular cysts, pronephric dilatation, and expansion of kidney cilia. In human fibroblasts and in a kidney spheroid model, GRK4 knockdown produced elongated primary cilia. Reconstitution with human wild-type GRK4 partially rescues these phenotypes. We found that kinase activity is dispensable because kinase-dead GRK4 (altered GRK4 that cannot result in phosphorylation of the targeted protein) prevented cyst formation and restored normal ciliogenesis in all tested models. Hypertension-associated genetic variants of GRK4 fail to rescue any of the observed phenotypes, suggesting a receptor-independent mechanism. Instead, we discovered unrestrained mammalian target of rapamycin signaling as an underlying cause. Conclusions: These findings identify GRK4 as novel regulator of cilia and of kidney development independent of GRK4's kinase function and provide evidence that the GRK4 variants believed to act as hyperactive kinases are dysfunctional for normal ciliogenesis.